EMPOWERING YOUNG LEARNERS: INTEGRATING CLIMATE CHANGE EDUCATION WITH BILINGUAL PICTURE BOOKS IN ELT - Putri, Cantika; Silvhiany, Sary; Inderawati, Rita (University of Kuningan, 2024)
Climate change is a global issue that impacts many people around the world. In recent years, several areas in South Sumatra have experienced the uneven impacts of climate change, especially forest fires and drought. Reflecting on the environmental problems that occur, this is closely related to the behavior of the community. Therefore, climate change education must be provided from the beginning, especially to young learners. This research, conducted at SD IT Harapan Mulia Palembang, aims to explore the potential of bilingual picture books in fostering a sense of responsibility and concern for the environment among young learners. By introducing climate change concepts in an accessible and relevant way, this study seeks to empower children to become advocates for environmental sustainability in their communities. Additionally, it aims to improve language skills and reading interest among young learners. This research involved 24 young sixth grade elementary school students, a stakeholder, and two English teachers through a mixed methods approach, questionnaires and semi-structured interviews.The findings of this research reveal the enthusiasm of young learners in using bilingual picture books about climate change in the classroom. Young learners have their own characteristics of books to use, some of which are based on themes and illustrations, story content, use of two languages, number of pages, and interactive elements such as crossword puzzles or short exercises that can hone their language skills. Therefore, researchers suggest that bilingual picture books can be developed and applied as effective and attractive learning media for young learners in English Language Teaching class.Keywords: climate change education; English for Young Learners; bilingual picturebooks; English language teaching